Eriodictyol Inhibits Proliferation, Metastasis and Induces Apoptosis of Glioma Cells via PI3K/Akt/NF-κB Signaling Pathway - Wenjun Li; Qian Du; Xiaoli Li; Xiangru Zheng; Feng Lv; Xin Xi; Guili Huang; Jia Yang; Songqing Liu (Frontiers Media S.A., 2020)
Glioma is the most common type of malignant brain tumor. Due to its highly aggressive and metastatic features, glioma is associated with poor prognosis and a lack of effective treatments. Eriodictyol, a natural flavonoid compound, has been reported to possess anti-inflammatory and antioxidant effects. However, the anti-tumor effects of eriodictyol and the underlying mechanisms have rarely been reported. In this study, we found that eriodictyol has anti-tumor activity in lung, colon, breast, pancreas, and liver cancer, and most significantly in glioma cell lines. Eriodictyol dose- and time-dependently suppresses cell proliferation, migration, and invasion in U87MG and CHG-5 glioma cells. In addition, eriodictyol induces apoptosis in U87MG and CHG-5 cells, as evaluated by flow cytometry, immunofluorescence, and Western blot. Furthermore, eriodictyol downregulates the phosphoinositide 3-kinase (PI3K)/Akt/NF-κB signaling pathway in a concentration-dependent manner. Moreover, the effects of eriodictyol on the apoptosis of glioma cells are enhanced by LY294002 (a PI3K inhibitor) and reversed by 740 Y-P (a PI3K agonist). In a mouse xenograft model, eriodictyol not only dramatically suppressed tumor growth but also induced apoptosis in tumor cells. In summary, our data illustrate that eriodictyol effectively inhibits proliferation and metastasis and induces apoptosis of glioma cell lines, which might be a result of the blockade of the PI3K/Akt/NF-κB signaling pathway.